La responsabilidad social corporativa y la cultura organizacional en la Cooperativa Visión de los Andes (Vis Andes). - Tacuri Saavedra, Cinthya Lizbeth (2025)
Corporate social responsibility is currently a demanding issue for companies since, through the initiatives and principles that it brings with it, it promotes commitment to society and, in turn, counteracts the effects that affect nature through sustainable projects over time. To implement CSR, it is essential to start with the organizational culture of the companies. In this case, the Cooperativa de Ahorro y Crédito Visión de los Andes (Vis Andes) promotes essential organizational culture principles to transmit trust and credibility among the company's staff, members, and clients. Furthermore, it must manage corporate social responsibility, as it allows for greater efficiency, is a competitive strategy within financial institutions, and generates a greater social focus in projects. In this context, the research considers it appropriate to identify the impact of social responsibility within the organizational culture of the Vis Andes Cooperative, Riobamba Agency. For this purpose, a theoretical and empirical background review is carried out to demonstrate the factors that explain the study variables and their role within the financial institution. For the study, we considered the members and clients corresponding to 2023. In contrast to the hypotheses, Pearson's Chi-Square test was used, the Gamma coefficient was used to test the intensity and direction between the variables, and the Sommers' D coefficient, which explains the dependence or independence between the variables. Finally, with the results obtained, the alternative hypothesis was accepted.